Bibliometric Analysis of Astrotourism as Sustainable Alternative Tourism - Judijanto, Loso; Syaefuddin, Achmad (West Science Social and Humanities Studies, 2025)
This study performs a thorough bibliometric examination of astrotourism as a sustainable alternative tourism sector, utilizing data from the Scopus and Web of Science databases (1990–2025). This research utilizes performance analysis and science mapping via VOSviewer and the Bibliometrix R-package to identify publication patterns, topic structures, and collaboration networks. The results indicate that astrotourism, dark sky, and sustainability are predominant terms, reflecting a robust relationship with sustainable tourism and environmental conservation principles. Emerging themes such as citizen science, application programs, and tourist behavior illustrate the field's increasing focus on innovation and community involvement. Institutional and national assessments indicate that Portugal, especially Universidade de Aveiro, excels in research output and international collaboration, connecting Europe with Africa, Asia, and Oceania. The paper conceptually contributes by delineating the intellectual framework of astrotourism and pinpointing research deficiencies concerning governance, technology, and tourist experience. It provides strategic insights for creating sustainable dark-sky destinations that incorporate science, culture, and community involvement.